PROSPECTS OF HOUSEHOLD SCALE VANAME SHRIMP FARMING BIOFLOC SYSTEM - Suderajad, Pono; Yusnaini, Yusnaini; Nur, Indriyani; A., Nurdiana (Universitas Mataram, 2025)
Soropia Village is a coastal area that is topographically potential for developing a biofloc shrimp farming business on a household scale, in addition this system reduces negative environmental impacts. However, it is necessary to study the potential in terms of the amount of costs, production potential and profits that can be obtained, and business feasibility. The research method used was a case study at the Bahari Jaya Group. Primary data was obtained using a survey technique through in-depth interviews regarding the variables needed in the analysis to achieve the research objectives. The results of the study showed that the largest investment cost was for the allocation of making a complete package pond, in the form of a D4 biofloc tarpaulin pond (4 meters in diameter) on a household scale of IDR 3,500,000.00. While the most dominant operational cost is the purchase of feed of IDR 1,800,000, but this amount is considered minimal in the vaname shrimp farming business, because of the biofloc element which is additional feed. The biofloc system vaname shrimp cultivation business on a household scale in 1 cycle maintained for 3 months, the total cost incurred was IDR 8,532,500, - and the production was 170 kg with a selling price of IDR 98,000 / kg, thus obtaining an income of IDR 16,660,000, -. The profit obtained was IDR 8,127,500, - with a business feasibility level of 1.9. This value is classified as feasible so that the biofloc system vaname shrimp cultivation business is very prospective to be implemented and applied on a household scale to improve the welfare of coastal communities.